Respostas

2013-08-08T13:48:56-03:00
A= a11  a12  
     a21  a22
     a31  a32
     a41  a42
     a51  a52

3i-3j

a11= 3.1-3.1
a11= 3-3
a11= 0

a12= 3.1-3.2
a12= 3-6
a12= -3

a21= 3.2-3.1
a21= 6-3
a21= 3

a22= 3.2-3.2
a22= 6-6
a22= 0

a31= 3.3-3.1
a31= 9-3
a31= 6

a32= 3.3-3.2
a32= 9-6
a32= 3

a41= 3.4-3.1
a41= 12-3
a41= 9

a42= 3.4-3.2
a42= 12-6
a42= 6

a51= 3.5-3.1
a51= 15-3
a51= 12

a52= 3.5-3.2
a52= 15-6
a52= 9


A= 0  -3
     3   0
     6  3
     9  6
    12  9


Segunda matriz:


A= ( a11  a12  a13 )

I2 + I3

a11= 1*2 + 1*3
a11= 2+3
a11= 5

a12= 1*2+2*3
a12= 2+6
a12= 8

a13= 1*2+3*3
a13= 2 +9
a13= 11

Os valores da matriz são respectivamente:

A= ( 5  9  11)